Dampak Bangkitan Lalu-Lintas Kawasan Ekonomi Khusus (KEK) Palu Terhadap Kinerja Perkerasan Jalan (Studi kasus Ruas Jalan Nasional Pantoloan-Tawaeli) - Hamid, A.G.; Bahar, T.; Setiawan, A. (Civil Engineering Department, Tadulako University, 2021)
Palu City is designated as a Special Economic Zone for the development of the region's economic potential, as an integrated logistics center and mining processing industry in the Sulawesi economic corridor to encourage equity and increase and accelerate the economy. The performance of road pavements will decrease as the road service ages. The impact of the existence of Palu Special Economic zone resulted in the rise/pull of new traffic movements that burdened the National Pantoloan-Tawaeli road section, This research was conducted under the guidance of Pavement Design Manual 2017, where from the results of the research there was traffic loading due to the existence of the Palu Special Economic Zone amounted to 997, 761, 256 CESAL, resulting in a reduction in the life of road services by 10 years.